Whose terrorists?: Libya and state criminality - Jenkins, Philip (Contemporary crises, 1988)
The government of Muammar Qaddafi has certainly engaged in ‘state criminality’ in acts of terrorism sponsored by official agencies of the Libyan state. However, these acts are nothing like as frequent or as systematic as has been suggested by Western critics. It is Qaddafi's weakness which leads to his stigmatization, rather than the true seriousness of his nation's crimes.In the last decade, there has been a dramatic growth of scholarly and journalistic work on terrorism, much of which uses the concept of ‘state terrorism’. That such a thing exists is clear. However, each case must be examined very closely before the motives and rationale for such a policy can be understood; and only then can we begin to address questions such as etiology. There could be a ‘criminology of states’ which would be a valuable addition both to criminology and political science. At present, though, our primary need is to understand that the facts in each case are often far different from the political rhetoric.